4x – 5 – 7x = 2 – 5x
2(x + 1) + 3(x – 2) = x + 4
4x – 5(3 – 2x) = 12 – 9(2x – 5)
(2x-5)/3 + (3-2x)/4 = 1
(2x-1)/6 - (5x-7)/3 = (3-2x)/2


daje naj



Odpowiedź :

Odpowiedź:

4x – 5 – 7x = 2 – 5x

-3x - 5 = 2 - 5x

2x = 7 /:2

x = 3,5

2(x + 1) + 3(x – 2) = x + 4

2x + 2 + 3x - 6 = x + 4

5x - 4 = x + 4

4x = 8 /:4

x = 2

4x – 5(3 – 2x) = 12 – 9(2x – 5)

4x - 15 + 10x = 12 - 18x + 45

14x - 15 = 57 - 18x

32x = 72 /:32

x=2,25

(2x-5)/3 + (3-2x)/4 = 1 /*12

4(2x-5) + 3(3-2x) = 12

8x - 20 + 9 - 6x = 12

2x = 23 /:2

x = 11,5

(2x-1)/6 - (5x-7)/3 = (3-2x)/2 /*6

1(2x-1) - 2(5x-7) = 3(3-2x)

2x - 1 -10x + 14 = 9 - 6x

4 = 2x /:2

2 = x

Szczegółowe wyjaśnienie: